Building capacity for a disability-inclusive response to violence against women and girls: experiences from the W-DARE project in the Philippines. Issue 2 (3rd May 2016) - Vaughan, Cathy; Devine, Alexandra; Ignacio, Raquel; Lacsamana, Wanet; Jesusa Marco, Ma.; Zayas, Jerome; Sobritchea, Carolyn
ABSTRACT: The Philippines has developed a range of national laws, policies, and programmes in response to violence against women and girls (VAWG). However, as elsewhere, the needs and experiences of women with disabilities are rarely considered in government policies or development activities. Yet women with disabilities are more likely to experience violence than their peers without disability, and they experience a range of barriers that prevent them accessing violence prevention and response services. This article describes initiatives supported by the W-DARE programme to respond to this. These initiatives have involved disabled people's organisations, local researchers, and activists in the women's movement, and officials from multiple levels of government. They aspire to build the ability of national policymakers, programme staff, and local service providers to respond to the interests of women and girls with disabilities who face violence.